2021
DOI: 10.1002/ehf2.13341
|View full text |Cite
|
Sign up to set email alerts
|

Parvovirus B19 DNA detectable in hearts of patients with dilated cardiomyopathy, but absent or inactive in blood

Abstract: Aims Parvovirus B19 (B19V) is often assumed to be a cause of dilated cardiomyopathy (DCM), based on the quantification of B19V DNA in endomyocardial biopsies (EMB). Whether the presence of B19V DNA correlates with active infection is still debated. Application of the enzyme endonuclease to blood samples results in degradation of B19V DNA remnants but leaves viral particles intact, which enables differentiation between active and past infection. In this study, the susceptibility to degradation by endonuclease o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 36 publications
2
1
0
Order By: Relevance
“…Nevertheless, stool samples from CTCL or PP patients have not been studied previously, since they are not routinely collected from this patient group. Previous studies on parvovirus B19 have shown that the parvovirus capsid protects the genome against nucleases like Benzonase 30,31 . In the current study, we were able to show, with the Benzonase‐PCR assay, the presence of protecting viral capsids in CuV PCR‐positive stools of two patients (one CTCL, one PP), suggesting that the patients were excreting infectious virions in their stools—despite their infections had persisted for at least 5 years.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Nevertheless, stool samples from CTCL or PP patients have not been studied previously, since they are not routinely collected from this patient group. Previous studies on parvovirus B19 have shown that the parvovirus capsid protects the genome against nucleases like Benzonase 30,31 . In the current study, we were able to show, with the Benzonase‐PCR assay, the presence of protecting viral capsids in CuV PCR‐positive stools of two patients (one CTCL, one PP), suggesting that the patients were excreting infectious virions in their stools—despite their infections had persisted for at least 5 years.…”
Section: Discussionsupporting
confidence: 61%
“…Previous studies on parvovirus B19 have shown that the parvovirus capsid protects the genome against nucleases like Benzonase. 30,31 In the current study, we were able to show, with the Benzonase-PCR assay, the presence possess the skin-tropic memory phenotype. 32 Furthermore, it is known that also malignant T cells in MF show great intra-tumoral genetic heterogeneity, 33 the implications of which in relation to CuV would also need to be examined.…”
Section: Discussionsupporting
confidence: 51%
“…Viral latency and active infection may alternate in individuals, accelerating LV dysfunction and development of DCM [142]. B19V is commonly found in EMBs of patients with DCM, whereas little to no correlation was found with blood virus titers, and no detection can be achieved with imaging, underlining the need for a comprehensive biopsy-driven diagnostic workup in cases of DCM of unclear etiology to allow for sufficient patient characterization [143]. Finally, the presence of B19V in the pediatric heart likely increases the risk of graft loss [103].…”
Section: Parvovirus B19mentioning
confidence: 99%
“…Due to an adult seroprevalence of 60%–70%, many recipients will not be susceptible [ 13 ]. Detectable DNA may originate from intact viral particles, causing true infection, or from DNA remnants released from previously infected cells [ 10 , 14–16 ]. Application of an endonuclease-based assay can differentiate between these 2 scenarios [ 10 ].…”
mentioning
confidence: 99%